Immunological Pathogenesis of Membranous Nephropathy: Focus on PLA2R1 and Its Role - Liu, Wenbin; Gao, Chang; Dai, Haoran; Zheng, Yang; Dong, Zhaocheng; Gao, Yu; Liu, Fei; Zhang, Zihan; Liu, Zhiyuan; Liu, Weijing; Liu, Baoli; Liu, Qingquan; et al. (Frontiers in Immunology, 2019)
Membranous nephropathy (MN) is the major cause of nephrotic syndrome with special pathological features, caused by the formation of immune complexes in the space between podocytes and the glomerular basement membrane. In idiopathic membranous nephropathy (IMN) the immune complexes are formed by circulating antibodies binding mainly to one of two naturally-expressed podocyte antigens: the M-type receptor for secretory phospholipase A2 (PLA2R1) and the Thrombospondin type-1 domain-containing 7A (THSD7A). Formation of antibodies against PLA2R1 is much more common, accounting for 70-80% of IMN. However, the mechanism of anti-podocyte antibody production in IMN is still unclear. In this review, we emphasize that the exposure of PLA2R1 is critical for triggering the pathogenesis of PLA2R1-associated MN, and propose the potential association between inflammation, pollution and PLA2R1. Our review aims to clarify the current research of these precipitating factors in a way that may suggest future directions for discovering the pathogenesis of MN, leading to additional therapeutic targets and strategies for the prevention and early treatment of MN.